Improving the Natural Science Learning Result through the Implementation of Teams Games Tournament Learning Model Aided with Video Learning - Putranto Adhi Nugroho; Elvira Hoesein Radia (Journal of Educational Science and Technology (EST), 2018)
The aim of this research is to know the improvement of student learning outcomes in science subjects using the cooperative model type TGT-assisted video learning media at grade IV SDN 02 Lebak Grobogan. This type of research is Research Action class. The subject of this research is the grade IV. Data collection used are tests, documentation, and observations. Data analysis technique used is the comparative descriptive analysis of quantitative data, i.e., Comparing test scores initial conditions, test scores after the cycle I and cycle II after the test value. The results of this study showed that after given learning by applying a model of education occurs learning video rocks TGT improved preconditions from cycle to cycle I and cycle II. An increase in the application of the model proves that media video-assisted learning TGT can improve the learning results of IPA students 4th grade State 02 Lebak Grobogan.